A Study of the Current State, Desired State and Needs Analysis for Supervisory Competency Development Base on Self- directed Learning under the Office of the Basic Education Commission - Somboon, Janista; Nantasri, Wanpen; Somsrisuk, Apisit (Dhammathas Academic Journal, 2022)
The purpose of this research was to Study of the Current State, Desired State and Needs Analysis for Supervisory Competency Development Base on Self-directed Learning Under the Office of the Basic Education Commission. The sample consisted of educational supervisors under the office of the basic education totally 335 which were obtained by multi-stage random. The instrument used was a 5-level rating scale questionnaire with the Index of item objective congruence (IOC) between 0.80-1.00, discrimination power value between 0.42-0.94, and the overall reliability value at 0.98. The data was analyzed by the calculations of frequency, percentage, average, standard deviation, PNImodified. The research results finds that: 1. The overall current state for supervisory competency development under the office of the basic education commission was a the high level and the overall desired state was at the highest level. 2. The mean of PNImodified for supervisory competency development under the office of the basic education commission was 0.31. The PNImodified index values in order of priority were as follows: Research (PNImodified = 0.38) Communication and Motivation (PNImodified = 0.34), Education Supervision (PNImodified = 0.32) and Teamwork (PNImodified = 0.21), Respectively.